Theoretical analysis of shape factor on performance of annular thermoelectric generators under different thermal boundary conditions. (15th January 2022) - Zhu, WenChao; Weng, Zebin; Li, Yang; Zhang, Leiqi; Zhao, Bo; Xie, Changjun; Shi, Ying; Huang, Liang; Yan, Yonggao
Abstract: The annular thermoelectric generator (ATEG) has received growing research interest due to its improved energy conversion efficiency compared to conventional flat-plate thermoelectric generators (FTEG). In this study, considering the influence of ceramic substrate and copper contact layer, a numerical model of the annular thermoelectric module (ATEM) was established for the studies of the influence of geometrical parameters on output performance under three typical application scenarios with different boundary conditions. It is found that when the heat flow on hot side is constant, the shape factors of the optimal performance are slightly different either if the convection coefficient or the temperature is considered constant on cold side. In both cases, the output power and the conversion efficiency decrease with the increase of the thickness of the thermocouple, and increase with the increase of the angle, length, and number of the thermocouples. When the temperatures are considered constant on both sides of the thermocouples, a conflicting relationship between the optimal output power and the efficiency exists. In this case, to obtain the best ATEG performance, multi-optimization problem is formulated and solved by the non-dominant sorting genetic algorithm with elite strategy method (NSGA-II). Highlights: A numerical model of ATEM considering ceramic substrate and copper contact layer. The shape factors of the optimal performance for ATEM are studied. The relationship between the output power, conversion efficiency and shape factors. A multi-optimization problem by the non-dominant sorting genetic algorithm with elite strategy method (NSGA-II).